Desain Gas Lift Dengan Metode Continuous Flow Untuk Mendapatkan Laju Alir Optimal Pada Sumur “F-1” Lapangan “X” - Dimas Putra Wibowo; M. Nur Mukmin; Rohima Sera Afifah; R.Bambang Wicaksono; Amiruddin; Luthfiyah Atisa Fadhilah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2021)
Well kick is the entry of formation fluid into the drill hole which causes formation pressure greater than the hydrostatic pressure of the drilling mud. The purpose of this study is to find out what factors cause a kick to occur, and how to repeat the kick using the wait and weight method. The wait and weight method is a kick countermeasures method with one circulation by new heavy mud. Steps to counteract well kick in the "MTM" well using the wait and weight method, namely by collecting drilling data, analyzing it with calculations of formation pressure when a kick occurs, hydrostatic pressure, KMW, ICP, FCP, maximum allowable mud weight, number of pump strokes , circulation time. Evaluate by comparing the calculation results with implementation data in the field, concluding the evaluation results. The results of the analysis of the implementation of well kick countermeasures using the wait and weight method obtained the initial formation pressure of 6888.16 psi, hydrostatic pressure of 6738.16 psi, KMW of 15.54 ppg, ICP of 1550 psi, FCP of 1431 psi, maximum allowable mud weight of 660.98 psi, total pump stroke was 0.1428 bbl/stk, and circulation time was 47,5 minutes. Well kick was successfully overcome using the wait and weight method.